Effect of Artesunate Treatment on Some Brain Biomolecules and its Behavioral Implication - Ekong, MB; Igri, AO; Ekanem, TB (Journal of Bangladesh Society of Physiologist, 2010)
Background: Artesunate (AS) is an artemisinin antimalarial drug used as a single drug or in combination with other antimalarials. Objective: This study was to find its effect on some brain biomolecules and behavioural activities in Wistar rats. Methods: Forty adult male Wistar rats weighing between 150- 180g were divided into four groups of A, B, C and D with 10 animals each. Group A served as the control that received tap water, while groups B, C and D served as the experimental groups that received 2.85mg/kg (therapeutic dose-TD) and 5.71mg/kg (high pharmacologic dose-HPD) of AS per day for 3 days, and 2.85mg/kg (long duration therapeutic dose -LDTD) of AS per day for six days respectively. Half of the dose was administered twelve hourly (twice a day), and twelve hours after the last treatments, behaviour test using the ‘open field maze' was carried out. Immediately after, the animals were sacrificed with chloroform anaesthesia and the whole brain removed and weighed. Whole brain homogenates were used to determine brain total protein (TP), triacylglycerol (TAG) and cholesterol (CH).Data were analyzed statistically by ANOVA and Tukey-Kramer Multiple Comparative Test as applicable. Results: There were no difference (p<0.05) between the experimental groups and the control group in the anthropometric parameters and behavioural activities. In the brain biomolecules concentration, TP was lower in concentration in the HPD group, TAG was lower in concentration in the LDTD group, while the HPD and LDTD groups had lower CH concentration compared to the control. In all the parameters studied no difference was found between the TD group and the control. Conclusion: AS at recommended dose may not affect some behaviour and brain biomolecule concentration, unlike when taken in excess of dose and or time. Even at these doses/time there may have been no behavioural manifestation. Key words: Artesunate, Brain, Anthropometry, Behavior, Biomolecules, Rats DOI: 10.3329/jbsp.v4i2.4171 J Bangladesh Soc Physiol. 2009 Dec;4(2): 44-50